(untitled) (Damascus University Journal of agriculture sciences, 2021)
Abstract 36 Shami cows were used in the Deir Al-Hajar Research Center for Shami Cattle Breeding to analyze the data of the nipple dimensions during the year 2019 to estimate some of the morphological indicators of the nipples and their relationship with the milk production of the Shami cows in Syria and to estimate the phenotypic relationships between the nipple dimensions with each other and with total milk production. The results showed a significant effect (P <0.05) for the parent cow’s season ranking on the characteristic of the left and right front and rear nipple length, as for the nipple diameter characteristic there was no significant difference, and the results showed a significant effect (P <0.05) for the cow season arrangement in the distance characteristic. Between the front nipples and the hind nipples, the distance between the left and right anterior nipples, and an increase in the distance between the nipples was observed with the progression of the season ranking, and the results indicated a significant difference (P <0.05) for the ranking of the cow’s season in characteristics after the nipples from the ground, where the first season cows outperformed Multiple-season cows, and the results showed a significant effect (P <0.05) for the production stage in measurements of the length of the right front and rear nipples and measurements of the diameter of the left rear nipples, the distance between the front nipples, the distance between the left anterior and posterior nipples, and the height of the nipples from the ground before and after milking. The results indicated that the first production phase outperformed the daily amount of milk produced over the second and third production stages, as well as the presence of a significant effect (P <0.05) for the ranking of the cow’s season in the total milk production. The multi-season cows died until the fourth on the first season cows slaughtered, and the results showed a high significant correlation (P <0.01) between the characteristics of measurements (the length of the left and right front nipples, and the left posterior) with measurements (the diameter of the left and right front nipples, and the left rear) before And after milking, the results also showed that there is a significant correlation between the mean of these measurements before and after milking with each other, and between the characteristics of measurements of the length and diameter of the nipples before and after milking and their averages, with the total milk quantity, which amounted to (r = 0.29, r = 0.33, r = 0.33. 0.25, r = 0.22, r = 0.33, r = 0.16, r = 0.34, r = 0.31), (r = 0.31, r = 0.22, r = 0.22, r = 0.27) respectively. It is concluded from the study: that the nipple measurements differ with the progression of the maternal cow’s season arrangement, and it was generally observed that the distance between the nipples increases with the progression of the mother’s season arrangement, and the distance between the nipples and the ground surface also decreases with the advancement of the maternal cow’s season order before and after milking, the milk production increases with the progression Arrange the season of the mother cow.